Ecology of Scaphium macropodum in the Sarolangun Jambi Production Forest Area - Lubis, Rizky Febriana Br; Marpaung, Sutan Sahala Muda; Srena, Mona Fhitri; Kusuma, Yosie Syadza; Batubara, Junianto S.; Siadari, Ulidesi (Jurnal Biologi Tropis, 2024)
The Pengulu Tribe in Limun District, Sarolangun Regency, Jambi Province, has long used the fruit of *Scaphium macropodum*—locally known as "merpayang" or "mempayang"—as a traditional medicine. *Scaphium macropodum* belongs to the Sterculiaceae family and has a broader distribution compared to its seven subspecies. This study investigates the ecology of *S. macropodum* to provide initial information on its use by the Pengulu Tribe, as well as the population and habitat conditions in Sarolangun Jambi's production forest. The study aims to estimate the population of *S. macropodum* in the forest and analyze the ecological factors influencing its habitat. Conducted between December 2023 and January 2024, the research utilized observation, interviews, and literature review methods, with data analyzed descriptively and qualitatively. Ecological factors were examined using the Importance Value Index (INP), diversity and evenness indices, community similarity index (Ward method), and Principal Component Analysis (PCA). The study identified 47 species from 18 tree families within the *S. macropodum* habitat. The dominant species in two research sites, APL NM and HA DM, were *Shorea parviflora* (meranti). At HL DT and APL DM, the dominant species were *Shorea multiflora* (squirrel coconut) and *Canarium* sp. (mosquito legs). The Shannon-Wiener diversity analysis indicated moderate diversity and evenness across the four sites. APL NM and HA DM had significant community similarity (90.81%), while APL DM had a lower diversity index compared to the other sites.